2019
DOI: 10.1101/553610
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The distribution of fitness effects among synonymous mutations in a gene under selection

Abstract: The fitness effects of synonymous mutations, nucleotide changes that do not alter the encoded amino acid, have often been assumed to be neutral, but a growing body of evidence suggests otherwise. We used site-directed mutagenesis coupled with direct measures of competitive fitness to estimate the distribution of fitness effects among synonymous mutations for a gene 15 under selection. Synonymous mutations had highly variable fitness effects, both deleterious and beneficial, resembling those of nonsynonymous mu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…More recent studies have revealed that synonymous changes have an underestimated effect on fitness through their perturbances before and during translation. Synonymous sequence variance can impact fitness by changing the stability of mRNA [40][41][42] and altering codons to perturb or better match the codon-anticodon ratio 43 . We have shown here that synonymous sequence can also be essential for ensuring parallel evolutionary outcomes across genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have revealed that synonymous changes have an underestimated effect on fitness through their perturbances before and during translation. Synonymous sequence variance can impact fitness by changing the stability of mRNA [40][41][42] and altering codons to perturb or better match the codon-anticodon ratio 43 . We have shown here that synonymous sequence can also be essential for ensuring parallel evolutionary outcomes across genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%